Optimalisasi Sumber Daya Manusia Melalui Pendampingan Pada UMKM Di Kelurahan Karangtengah - Anita Wulandari; Rizky Dermawan (Institut Nalanda, 2023)
Business development efforts require the performance of qualified human resources. That way one can see the potential of a person in managing his business. But today there are still MSMEs actors who lack the knowledge to make progress in their business. Group 32 helps business actors by sharing knowledge, namely through socialization and mentoring. It is hoped that this activity can help improve the quality of business to be wider and have a network of relationships. The implementation of this activity uses training and mentoring methods in the form of socialization of digital product marketing and product photography training.